Multiculturalism and minority rights in the Arab world - Kymlicka, Will; Pföstl, Eva (Oxford University Press, 2014)
This title explores the obstacles to multiculturalism and minority rights in Arab states, including the history of European manipulation of minority politics.
Includes index.
Keywords: Multiculturalism -- Arab countries.; Minorities -- Legal status, laws, etc. -- Arab countries.; Multiculturalisme -- États arabes.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Minorities -- Legal status, laws, etc.; Multiculturalism; Arab countries; Arabische Staaten; Arab States.; Minorities.; Human rights.; Multicultural society.